Mechanical advantage assurance control of quick-return mechanisms in task space - Mendoza, Jocabed; Perrusquía, Adolfo; Flores-Campos, Juan Alejandro (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Quick-return mechanisms are usually controlled by joint-space controllers to avoid instability in the transition between cutting and return phases. These controllers cannot exploit the mechanical advantage associated to the natural mechanism's movement in the task space. It is crucial to guarantee mechanical advantage exploitation to reduce operation time and high-quality cutting finishes. In view of the above, this paper reports the design of a mechanical advantage assurance controller based on: i) a slider physics model that captures all the information associated to the main mechanism's task, and ii) a Jacobian compensator that avoids the controllability problems from the transition between the cutting and return phases. Simulation studies are carried out to verify each component of the proposed controller. A constant cutting velocity task is used as a case of study to demonstrate the mechanical advantage exploitation.